Developing a Word Composition Educational Game for Young Children After the Covid-19 Pandemic - Akbar Iskandar (Ceddi Journal of Education, 2022)
The purpose of this study is to develop a word composition educational game for young children after the Covid-19 pandemic. The game is designed to help children strengthen their word composition skills and introduce new letters and syllables related to fruits. The game uses a 2D display and is developed using the Construct 2 game engine. The development method used is the waterfall method, and the game was tested on 10 parents and teachers to validate its effectiveness in helping children learn to compose words. The results of the study showed that the use of gamification and technology in early childhood education can help to motivate children and improve their learning outcomes. The use of Construct 2 as a game engine allowed for the development of a user-friendly and visually appealing educational game. The contribution of this study is to provide an innovative solution for improving children's word composition skills in a fun and engaging way.